Survei Kemampuan Kondisi Fisik Peserta Kegiatan Ekstrakurikuler Sepakbola SMP - Alfaridhi, Fani; Nurrochmah, Siti (Universitas Negeri Malang, 2021)
Abstract: The purpose of this study was to determine and assess the ability of the physical condition of the participants in the football extracurricular activities at SMP Negeri 15 Malang. This study used a quantitative descriptive survey design. The subjects of this study were 30 participants in extracurricular football activities at SMP Negeri 15 Malang. The data was collected using a test form measurement technique, namely a test of the ability of the physical condition in the form of a test of motion agility, movement speed, flexibility of motion and leg muscle explosive power. The results of data analysis on the participants of the extracurricular football activities at SMP Negeri 15 Malang included (1) shuttle run agility 43, 3% medium category (2) running speed 50 m 5.33% medium category (3) body flexibility sit and reach 43.3% medium category and (4) leg muscle explosive power standing board jump 33.3% moderate category. Based on the results of the study, it was concluded that the participants of extracurricular football activities at SMP Negeri 15 Malang, the physical condition of the agility element was included in the